2017
DOI: 10.1051/metal/2017033
|View full text |Cite
|
Sign up to set email alerts
|

Conventional and microwave assisted sintering of copper-silicon carbide metal matrix composites: a comparison

Abstract: This study investigates the effect of heating mode on the sintering of Copper-SiC metal matrix composites containing up to 7.5 wt.% SiC. The sinterability of the Cu-SiC system consolidated in a 2.45 GHz multimode microwave furnace has been critically compared with that processed in a radiatively heated (conventional) furnace. As compared to conventional sintering, microwave processing has resulted in a greater densification. It was observed that an increase in SiC content resulted in a higher hardness of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Mechanically milled Cu-LaB6 powders were consolidated using microwave sintering (MS) and spark plasma sintering (SPS) to produce specimens with a diameter of about 13 mm and a height of about 25 mm (Figure 1). According to a literature review (Ngai et al, 2013;Ayyappadas et al, 2017;Sathish et al, 2019;Pellizzari and Cipolloni, 2020), in this study, the optimum values for the production parameters in MS and SPS methods used to produce ceramic particle-reinforced Cu matrix composites were determined, and these values were taken as high as possible in order to achieve higher density, which leads to better mechanical and physical properties such as compressive strength and electrical conductivity, as well as to avoid excessive grain growth, which has a negative effect on the properties of the materials. Prior to the microwave sintering process, powders were pressed at a pressure of 400 MPa in a steel mold.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanically milled Cu-LaB6 powders were consolidated using microwave sintering (MS) and spark plasma sintering (SPS) to produce specimens with a diameter of about 13 mm and a height of about 25 mm (Figure 1). According to a literature review (Ngai et al, 2013;Ayyappadas et al, 2017;Sathish et al, 2019;Pellizzari and Cipolloni, 2020), in this study, the optimum values for the production parameters in MS and SPS methods used to produce ceramic particle-reinforced Cu matrix composites were determined, and these values were taken as high as possible in order to achieve higher density, which leads to better mechanical and physical properties such as compressive strength and electrical conductivity, as well as to avoid excessive grain growth, which has a negative effect on the properties of the materials. Prior to the microwave sintering process, powders were pressed at a pressure of 400 MPa in a steel mold.…”
Section: Methodsmentioning
confidence: 99%
“…It was found that while the thermal conductivities of Cu-SiC composites manufactured by SPS and hot pressing methods decreased with an increase in the amount of SiC particles, the thermal conductivity of specimens produced by the SPS method was higher than that of specimens produced by the hot pressing method (Chmielewski et al, 2017). Ayyappadas et al investigated the effects of microwave-assisted sintering versus conventional sintering on the electrical conductivity and hardness of Cu-SiC composites (2.5, 5, and 7.5 wt.%) (Ayyappadas et al, 2017). It was reported that as the weight fraction of SiC particles increased, hardness increased but electrical conductivity decreased, and it was shown that the electrical conductivity and hardness of Cu-SiC composites produced by microwave sintering were higher than those of conventional sintering specimens.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that MWS delivered a larger sintered thickness, more prominent densification, and superior mechanical characteristics as compared to CS. The impact of heating mode on the sintering of Copper-SiC metal matrix composite was investigated by Ayyappadas et al [ 9 ]. They found that MWS resulted in a significant densification as compared to regular sintering.…”
Section: State Of Artmentioning
confidence: 99%
“…Our previous works have demonstrated that microwave synthesis offers several advantages, such as reduced time, temperature, and energy costs during the synthesis process [18][19][20][21][22]. Additionally, the application of microwave energy to radio-absorbing materials, by means of the ponderomotive effect and electrodiffusion, enhances the characteristics of the phosphors [23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%